Impact of Socioeconomic Factors on Schoolboys’ Academic Performance and Psychological Well-being: Exploring Learning Challenges and Emotive Distress - Muzamil Hussain AlHussaini; Muhammad Shah; Muhammad Ahmar Jamshaid (JCTE, 2025)
This study looks into the multidimensional relationship between socioeconomic status, academic achievement, and mental health in pupils. The study seeks to investigate the complex interplay between socioeconomic status (SES), educational obstacles, and emotional distress, as well as their impact on students' overall well-being. The study was quantitative in nature, and a descriptive approach was chosen. District Bhakkar and District Layyah public institutes were population of the research study. With the help of five likert scale questionnaire data were collected and SPSS used for statistical analysis. This study a complete review of review of literature and analyzes the number of elements analyzed of how much differences of socioeconomic (SES) appear in learning backgrounds and how academic performance of students affected and as well as their intellectual well-being. More than a few such factors effect educational achievement and psychological health which related to their income & level of education of their parents and also family structure and resource access. Moreover this research study gazed different ways that (SES) dynamics influence anxiety and depression of learners and as well as their intellectual health.